Absence of the Caspases 1/11 Modulates Liver Global Lipid Profile and Gut Microbiota in High-Fat-Diet-Induced Obese Mice - de Sant'Ana, Lívia Pimentel; Ribeiro, Dalila Juliana S.; Martins, Aline Maria Araújo; dos Santos, Fábio Neves; Corrêa, Rafael; Almeida, Raquel das Neves; Eberlin, Marcos Nogueira; Maurice, Corinne F.; Magalhães, Kelly Grace (Frontiers in Immunology, 2020)
Obesity is a chronic disease with rising worldwide prevalence and largely associated with several other comorbidities, such as cancer, nonalcoholic fatty liver disease (NAFLD) and metabolic syndrome. Hepatic steatosis, a hallmark of NAFLD, is strongly correlated with obesity and has been correlated with changes in the gut microbiota, which can promote its development through the production of short-chain fatty acids (SCFAs) that regulate insulin resistance, bile acid, choline metabolism, and inflammation. Recent studies have suggested a controversial role for the inflammasome/caspase-1 in the development of obesity and nonalcoholic steatohepatitis (NASH). Here, we evaluated the role of inflammasome NLRP3 and caspases 1/11 in the establishment of obesity and hepatic steatosis in diet-induced obese mice, correlating them with the global lipid profile of the liver and gut microbiota diversity. After fed wild type, caspases 1/11, and NLRP3 knockout mice with a standard fat diet (SFD) or a high fat diet (HFD), we found that the caspases 1/11 knockout mice, but not NLRP3 knockout mice, were more susceptible to HFD-induced obesity and developed enhanced hepatic steatosis even under SFD conditions. Lipidomics analysis of the liver, assessed by MALDI-MS analysis, revealed that the HFD triggered a significant change in global lipid profile in the liver of WT mice compared to those fed an SFD, and this profile was modified by the lack of caspases 1/11 and NLRP3. The absence of caspases 1/11 was also correlated with an increased presence of triacylglycerol in the liver. Gut microbial diversity analysis, using 16S rRNA gene sequencing, showed there was also an increase of Proteobacteria and a higher Firmicutes/Bacteroidetes ratio in the gut of caspases 1/11 knockout mice fed an HFD. Overall, mice without caspases 1/11 harbored gut bacterial phyla involved with weight gain, obesity, and hepatic steatosis. Taken together, our data suggest an important role for caspases 1/11 in the lipid composition of the liver and in the modulation of the gut microbial community composition. Our results further suggest that HFD-induced obesity and the absence of caspases 1/11 may regulate both lipid metabolism and gut microbial diversity, and therefore may be associated with NAFLD and obesity.